2021
DOI: 10.5194/acp-2021-270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An organic crystalline state in ageing atmospheric aerosol proxies: spatially resolved structural changes in levitated fatty acid particles

Abstract: Abstract. Organic aerosols are key components of the Earth’s atmospheric system. The phase state of organic aerosols is known to be a significant factor in determining aerosol reactivity, water uptake and atmospheric lifetime – with wide implications for cloud formation, climate, air quality and human health. Unsaturated fatty acids contribute to urban cooking emissions and sea spray aerosols. These compounds, exemplified by oleic acid and its sodium salt, are surface active and have been shown to self-assembl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 92 publications
1
12
0
Order By: Relevance
“…This lamellar phase is liquid crystalline, as opposed to the crystalline lamellar phase observed previously in levitated particles (Milsom et al, 2021a). This is due to the lack of characteristic wide-angle X-ray scattering (WAXS) peaks returned by these samples (Milsom et al, 2021b), characteristic of the crystalline form of this lamellar phase (Tandon et al, 2001;Milsom et al, 2021a). Liquid oleic acid does exhibit some order via the formation of dimers.…”
Section: Introductionmentioning
confidence: 76%
“…This lamellar phase is liquid crystalline, as opposed to the crystalline lamellar phase observed previously in levitated particles (Milsom et al, 2021a). This is due to the lack of characteristic wide-angle X-ray scattering (WAXS) peaks returned by these samples (Milsom et al, 2021b), characteristic of the crystalline form of this lamellar phase (Tandon et al, 2001;Milsom et al, 2021a). Liquid oleic acid does exhibit some order via the formation of dimers.…”
Section: Introductionmentioning
confidence: 76%
“…4). The formation of a surface crust has been postulated in the literature (Pfrang et al, 2011;Zhou et al, 2013) and direct experimental evidence of surface product aggregation has recently been presented in a similar proxy (Milsom et al, 2021a).…”
Section: Spatial and Temporal Evolution Of Composition And Diffusionmentioning
confidence: 96%
“…This is a long-standing discrepancy and suggests that some physical process is inhibiting the ageing of such aerosols. For these reasons, oleic acid has been the compound of choice for laboratory studies into aerosol heterogeneous oxidation (Gallimore et al, 2017;King et al, 2020;Milsom et al, 2021bMilsom et al, , 2021aPfrang et al, 2017;Woden et al, 2021;Zahardis and Petrucci, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of α-pinene in the droplet phase was more than 1 order faster than in bulk aqueous solutions, likely due to more effective diffusion of ozone in the gas phase and more efficient mass accommodation at the air-droplet interface (King et al, 2008). Milsom et al (2021) reported the ozonolysis of fatty-acid-soap mixed particles, using oleic acid and sodium oleate as models. In these particles, the strong interactions between the soap carboxylate and the carboxylic acid form crystalline structures (Milsom et al, 2021).…”
Section: Multiphase Oxidation Of Aerosol Particlesmentioning
confidence: 99%
“…Milsom et al (2021) reported the ozonolysis of fatty-acid-soap mixed particles, using oleic acid and sodium oleate as models. In these particles, the strong interactions between the soap carboxylate and the carboxylic acid form crystalline structures (Milsom et al, 2021). Upon ozonolysis, the decay of C=C (∼ 1600 cm −1 ) was faster in liquid oleic acid droplets than crystalline oleic-acid-soap particles, although the crystalline structure was eventually broken by ozonolysis.…”
Section: Multiphase Oxidation Of Aerosol Particlesmentioning
confidence: 99%